What plant breeding may (and may not) look like in 2050? - Bassi, Filippo; Sanchez-Garcia, Miguel; Ortiz, Rodomiro (Crop Science Society of America, 2023)
At the turn of 2000 many authors envisioned future plant breeding. Twenty years after, which of those authors’ visions became reality or not, and which ones may become so in the years to come. After two decades of debates, climate change is a “certainty,” food systems shifted from maximizing farm production to reducing environmental impact, and hopes placed into GMOs are mitigated by their low appre ciation by consumers. We revise herein how plant breeding may raise or reduce genetic gains based on the breeder’s equation. “Accuracy of Selection” has signif icantly improved by many experimental-scale field and laboratory implements, but also by vulgarizing statistical models, and integrating DNA markers into selection. Pre-breeding has really promoted the increase of useful “Genetic Variance.” Short ening “Recycling Time” has seen great progression, to the point that achieving a denominator equal to “1” is becoming a possibility. Maintaining high “Selection Intensity” remains the biggest challenge, since adding any technology results in a higher cost per progeny, despite the steady reduction in cost per datapoint. Further more, the concepts of variety and seed enterprise might change with the advent of cheaper genomic tools to monitor their use and the promotion of participatory or cit izen science. The technological and societal changes influence the new generation of plant breeders, moving them further away from field work, emphasizing instead the use of genomic-based selection methods relying on big data. We envisage what skills plant breeders of tomorrow might need to address challenges, and whether their time in the field may dwindle.